A solid-phase transfection platform for arrayed CRISPR screens - Serçin, Özdemirhan; Rein, Katrin; Halavatyi, Aliaksandr; Winter, Hauke; Abdollahi, Amir (Molecular systems biology, 2019)
Abstract Arrayed CRISPR-based screens emerge as a powerful alternative to pooled screens making it possible to investigate a wide range of cellular phenotypes that are typically not amenable to pooled screens. Here, we describe a solid-phase transfection platform that enables CRISPR-based genetic screens in arrayed format with flexible readouts. We demonstrate efficient gene knockout upon delivery of guide RNAs and Cas9/guide RNA ribonucleoprotein complexes into untransformed and cancer cell lines. In addition, we provide evidence that our platform can be easily adapted to high-throughput screens and we use this approach to study oncogene addiction in tumor cells. Finally demonstrating that the human primary cells can also be edited using this method, we pave the way for rapid testing of potential targeted therapies.